(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The purpose of the article is to investigate the peculiarities of strategic management of higher educational institutions and to offer your own vision of the use of strategic marketing in it. Methodological basis of researches were scientific works of scientists in strategic management, marketing, management of higher education. The proposed approaches to building the process of marketing strategic planning of universities can be taken into account by higher education institutions when setting strategic goals and developing a marketing strategy at the university level and at the level of the faculty. The article analyzes the place of the marketing strategy in the structure of the general planning of the university activities, it is noted that the definition of the mission is the primary element of the process of marketing strategic planning, but it should be accompanied by marketing strategic analysis, since without the analysis the mission will be unreasonable and there will be a risk of direction of the activity of the university in the wrong direction; the main varieties of marketing strategies of higher educational institutions are determined; highlights the expediency of developing a university strategy with a thorough understanding of both the market of educational services and the labor market, assessing their strengths and weaknesses, as well as recognizing their rivalry advantages; on the basis of preliminary analysis the process of marketing strategic planning of higher education institutions is formed; highlights the necessity of marketing current segmentation of educational services market, analysis of market segments and selection of target segments within faculties, formation of marketing positioning purposes. It was emphasized that in the area of concourse the school should put forward two main strategies: low prices and differentiation. Categories of «current marketing segmentation» and «strategic marketing segmentation» are distinguished: the current analysis involves analyzing a segmental market structure that has already developed at a certain point in time; the strategic goal is to find unsatisfied and promising market needs. Depending on the strategic areas of the university, it is proposed to allocate three main strategic levels: general university level, level of faculties, level of educational programs. The conclusion is made that ensuring the improvement of the quality of educational services. is achieved in conditions of optimization of management, introduction of marketing strategic management. The main varieties of marketing strategies of universities are: general marketing strategies of universities (growth); marketing strategy of competition; strategy of segmentation and positioning, strategy of elements of the marketing complex.